2010
DOI: 10.1111/j.1365-2516.2010.02223.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in haemophilia patients with inhibitors, with special emphasis on orthopaedics: Madrid experience

Abstract: Summary. We report on a series of 92 surgical procedures (90 patients). It includes 35 orthopaedic procedures (33 patients) and 57 non-orthopaedic procedures (57 patients). The orthopaedic procedures include 27 radiosynovectomies (minor surgery) and eight major orthopaedic procedures. The non-orthopaedic procedures include 52 minor interventions and five major procedures. The average age of patients was 34 years (range: 8-56), and the average follow-up time was 3 years (range: 1-6). Of the 92 surgical procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…Oslo University Hospital, Oslo, Norway procedures performed using aPCC as replacement therapy in patients with inhibitors [2][3][4][5][6][7][8][9][10]. The hemostatic efficacy in these case series have been reported from 78% to 100%.…”
Section: Pål Andrè Holmementioning
confidence: 99%
See 1 more Smart Citation
“…Oslo University Hospital, Oslo, Norway procedures performed using aPCC as replacement therapy in patients with inhibitors [2][3][4][5][6][7][8][9][10]. The hemostatic efficacy in these case series have been reported from 78% to 100%.…”
Section: Pål Andrè Holmementioning
confidence: 99%
“…However, experience during the last 10-15 years using bypassing agents has shown that, despite increased bleeding risk compared to noninhibitor patients, the results are in general good [1][2][3][4][5][6][7][8][9][10][11][12]. However, experience during the last 10-15 years using bypassing agents has shown that, despite increased bleeding risk compared to noninhibitor patients, the results are in general good [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Close collaboration and communication among the MDT members and the patient/family is vital throughout . Surgery in inhibitor patients remains the most challenging area and should only be conducted at an HTC by an experienced, specialized MDT …”
Section: Introductionmentioning
confidence: 99%
“…However, for those with high‐titre inhibitors (≥5 BU), bypassing agents that circumvent the need for factor VIII (FVIII) or FIX concentrates are used to achieve haemostasis. Until recently, perioperative prophylaxis with bypassing agents was not considered in congenital haemophilia with inhibitors (CHwl) , and elective (especially major) surgery was rarely performed . Consequently, potentially beneficial surgeries and invasive screening procedures may have been deferred in this population, to the detriment of affected patients .…”
Section: Introductionmentioning
confidence: 99%